The design thinking playbook : mindful digital transformation of teams, products, services, businesses and ecosystems - Lewrick, Michael, ....-; Link, Patrick, ....-; Leifer, Larry J., ....- (Hoboken : Wiley, 2018)
"The Design Thinking Playbook is an actionable guide to the future of business. By stepping back and questioning the current mindset, the faults of the status quo stand out in stark relief—and this guide gives you the tools and frameworks you need to kick off a digital transformation. Design Thinking is about approaching things differently with a strong user orientation and fast iterations with multidisciplinary teams to solve wicked problems. It is equally applicable to (re-)design products, services, processes, business models, and ecosystems. It inspires radical innovation as a matter of course, and ignites capabilities beyond mere potential. Unmatched as a source of competitive advantage, Design Thinking is the driving force behind those who will lead industries through transformations and evolutions. This book describes how Design Thinking is applied across a variety of industries, enriched with other proven approaches as well as the necessary tools, and the knowledge to use them effectively. Packed with solutions for common challenges including digital transformation, this practical, highly visual discussion shows you how Design Thinking fits into agile methods within management, innovation, and startups. Explore the digitized future using new design criteria to create real value for the user Foster radical innovation through an inspiring framework for action Gather the right people to build highly-motivated teams Apply Design Thinking, Systems Thinking, Big Data Analytics, and Lean Start-up using new tools and a fresh new perspective Create Minimum Viable Ecosystems (MVEs) for digital processes and services which becomes for example essential in building Blockchain applications Practical frameworks, real-world solutions, and radical innovation wrapped in a whole new outlook give you the power to mindfully lead to new heights.--
From systems and operations to people, projects, culture, digitalization, and beyond, this invaluable mind shift paves the way for organizations—and individuals—to do great things. When you're ready to give your organization a big step forward, The Design Thinking Playbook is your practical guide to a more innovative future."
Includes bibliographical references and index.
Keywords: Creative ability in business; Creative ability in technology; Creative thinking; Industrial management -- Technological innovations; Technological innovations